The Effect of Non-Financial and Financial Factors on the Timeliness of the Submission of Company Annual Financial Statements - Fatikhatul Aula; Sasongko Budisusetyo (STIE Perbanas Surabaya, 2018)
Timeliness is the availability of information for decision makers at the right time so that it can infl uence the stakeholders’ decisions. The aim of this study is to examine the effect of fi nancial and non-financial factors on the timeliness of the submission of company annual fi nancial statements. The population consists of manufacturing companies listed on the Indonesia Stock Exchange 2012-2016. A sample of 243 companies were obtained using a Purposive sampling method. The data processed by suing SPSS version 23 with descriptive analysis and multiple linear regression analysis. Based on the results of this study, the variables of independent board of commissioners and profi tability have a signifi cant effect on the timeliness of the submission of company annual fi nancial statements, while the variables of public ownership, institutional ownership, audit tenure, leverage, and fi rm size have no signifi cant effect on the timeliness of the submission of company annual fi nancial statements.